The Willingness to Pay of Overseas’ Tourists on Visiting Ecotourism at Phou Khao Khouay National Conservation Area, Vientiane Capital, Laos - Xainhiaxang, Khamsaolee; Nhiacha, Chucheeyang; Photisut, Lyxay; Sisouphanthong, Viriyasack; Khang, Yiakhang; Kyophilavong, Phouphet; Chanthanivong, Thongpheth (International Journal of Multidisciplinary in Management and Tourism, 2020)
This paper is to estimate the Willingness to Pay (WTP) of overseas tourists on visiting Phou Khao Khouay conservation area, Vientiane Capital. The analysis relied on Choice Modeling (CM): Conditional Logit with interaction to seek out to identify the factors that affect the WTP. We used the attribute variables and non-attribute variables to analyze which are Camping, Hiking, Waterfall activities and culture, and religion visiting. On this paper, we subdivide to two types of WTP, first WTP on general conditional logit model, and second is the conditional logit with interaction. According to the sample of 315 respondents, the consequences showed that the WTP of tourists from the first model on the waterfall is the highest which is 74.8 USD, followed by Hiking, Camping and religion, and culture which are accounted for 65.52 USD, 44.02 USD and 32.85USD respectively. The second model, we found that the WTP of tourists on the waterfall is which is 86.27 USD, followed by Hiking, Camping, and religion, and culture which are accounted for 52.82 USD, 39.94 USD and 30.67USD. Based on the analysis, the all socio-economic characteristics of respondents have not statistically significant, it means that the personal characteristics have not directly affected on WTP. These findings do not only support the provision of good and green services in Phou Khao Khuay conservation area but will also be useful for the whole ecotourism in Laos.